Performance Analysis of a Novel TCP Protocol Algorithm Adapted to Wireless Networks - Gonzalo Olmedo; Román Lara-Cueva; Diego Martínez; Celso de Almeida (Future Internet, 2020)
As telecommunication systems evolve towards new-generation architectures, likewise, new protocols are created in order to improve efficiency. One of these protocols is Transmission Control Protocol (TCP), which controls the transmission bit rate in function of network congestion. Nevertheless, in wireless communications, there appear problems such as noise and interference, for which TCP was not designed. Based on these problems, there exist some methods trying to mitigate congestion, such as explicit loss notifications and the use of end-to-end codification. The aim of this work was to propose a wireless TCP protocol improvement, considering a negative acknowledgment (NACK), which allows to differentiate between losses due to congestion and losses due to wireless channel issues. NACK employs a small protocol packet and produces improvement in the quality of service metrics. The experiments were carried out in in-door and out-door environments, over an online video game scenario, and over a long-distance wireless link between two islands. The average results show a 25-percent delay improvement and a 5-percent jitter improvement when compared to the original TCP Reno protocol, while for throughput a 90-percent improvement was achieved for distances between 100 and 414 m.